Design and development of elective courses recommender system (ECORS) - Eng, Pei Wen (Universiti Malaysia Sarawak (UNIMAS), 2017)
Choosing elective courses is important for all undergraduates student in Universiti Malaysia Sarawak (UNIMAS). There are vast number of courses available and student might lack of awareness of which courses to follow. This project aimed to design and develop an elective course recommender system for the purpose of providing recommendation of elective courses based on student's interest. A rule-based algorithm is chosen to use in this project. It combines normalized scores representing variables such as interest score including a student's personal interests. This creates a final normalized score for each course. Ultimately, the courses with the highest interest scoring are passed on to the User Interface. Usability testing is conducted in system evaluation process using questionnaire adapted from Recommender systems' Quality of user experience (ResQue). The main purpose is to examine the user's experience towards ECQRS in terms of quality of recommended items, interaction adequacy, interface adequacy. perceived ease of use, perceived usefulness and attitudes toward system.